(untitled) (Innovaciones Educativas, 2021)
In the Costa Rican educational system, the approval of the educational policy accentuates the community management processes as an element for the autonomy of the educational institutions. This study aims to analyze community management construction indicators from the head teachers’ perspective. The methodology is based on a mixed approach with a sequential design; in phase I, qualitative information was collected through focus groups, and in phase II, quantitative information was survey gathered with the participation of the headteachers of the Ministry of Public Education, specifically of the Regional Educational Councils of Pérez Zeledón and San Carlos. The results show the need to build community management indicators that allow education managers to strengthen management, specifying decisions and actions at a community level. In addition, it is essential to generate evaluation and monitoring mechanisms to achieve autonomy for educational institutions.